The Effect of Postsecondary Educational Institutions on Local Economies: A Bird's-Eye View - Patrick Lehnert; Madison Dell; Uschi Backes-Gellner; Eric Bettinger (Institute of Labor Economics (IZA), 2024)
Despite worldwide expansion of higher education, the impact of higher education institutions on local economic activity is still poorly understood. We analyze the local economic effects of branch campus openings in Tennessee and Texas, two states representative of the underlying U.S. enrollment patterns. To overcome the lack of adequate data, we use a novel proxy for regional economic activity based on daytime satellite imagery. Applying different panel methods—traditional difference-in-differences (DD), heterogeneity-robust DD, and instrumental variables—we find positive effects. Independent data show an increase in college graduates and employment in the sectors aligned with programs offered at branch campuses.
Keywords: I23; I25; I26; R12; 330; postsecondary education; regional economic development; higher education; social returns to education